Radon concentration assessment in water sources of public drinking of Covilhã's county, Portugal - Inácio, M. (2017)
Radon, the heaviest of the noble gases on the periodic table of elements, is a natural radioactive element that can be found on water, soils and rocks. The main goal of this work is to present an evaluation of radon concentration on samples of water, used for human consumption, collected on uranium-rich granitic rock areas. Once the geological features of the sampling region evidence the presence of this natural radionuclides, their slow dissolution steadily increases concentration in ground water. Although, the most important contribution of natural radiation, for most populations, is from inhaled radon (generic term used commonly to refer to the isotope 222Rn), in some circumstances, exposure to natural radionuclides, through drinking water, could exceed acceptable levels, and also present a hazard. Despite the fact that radon can be reduced if the water is boiled, this gas, dissolved in ground water, can be released into the air during household activities such as showering, dishwashing and laundry. So, the short lived radon decay products will contribute to increase the number of those which are present in particles suspended in the indoor air and can be accumulated up to dangerous concentrations. Once the radon progeny emits highly ionizing alpha-radiation, they may cause substantial health damage after long-term exposure. Radon concentration measurements were performed on thirty three samples collected from water wells at different depths and types of aquifers, at Covilhã's County, Portugal with the radon gas analyser DURRIDGE RAD7. Twenty three, of the total of water samples collected, gave, values over 100 Bq/L, being that 1690 Bq/L was the highest measured value.